ALISHER NAVOIY ASARLARINI O’QITISHDA MEDIAPEDAGOGIKANING O’RNI - Zamonova, F.U. (SCIENCE and SOCIETY, 2022)
This article discusses the role of modern information technology in the study of Alisher Navoi's works. The role and effectiveness of mobile applications is analyzed in teaching and strengthening the knowledge of Navoi's, work. Through mobile games, students can consolidate their knowledge.
Keywords: educational process; modern information technologies; education system; mobile applications; mobile games; the epic "Saddi Iskandariy"; electronic textbooks; player portfolio